Global nutrition leaders have applied learning from the Transforming Nutrition course in their work as program practitioners and policy makers - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
Participants in the innovative ‘Transforming Nutrition: Ideas, Policies and Outcomes’ course have applied the knowledge and evidence they gained from the course to specific national and sub-national situations in their home countries to identify strategic areas for nutrition action. The curriculum, designed and taught by the Institute for Development Studies (IDS) and researchers from IFPRI incorporates evidence from, among others, CGIAR research and engagement around both nutrition-sensitive and nutrition-specific actions.